Peningkatan Hasil Belajar Lokomotor Melalui Permainan Tradisional Hadang - Aswar, Aswar; Arfanda, Poppy Elisano; Ishak, Muhammad; Hasmyati, Hasmyati; Hudain, Muh. Adnan (Prodi Pendidikan Jasmani dan Olahraga, 2025)
This research aims to improve the learning outcomes of students' locomotor movement skills through the application of traditional chess games in grade IV of elementary school. This study uses the class action research method (PTK) which is carried out in two cycles. Each cycle consists of planning, execution, observation, and reflection. The subjects of the study were 20 grade IV students, and data were collected through a locomotor motion skill test. The results showed a significant improvement in student learning outcomes. In the pre-Cycle, only 5% of students achieved the completion criteria, while in Cycle I, the number increased to 55%. In Cycle II, 95% of students achieved the completion criteria, with 75% of students in the